A demanda por empregos em ocupações intensivas de conhecimento nos parques científicos e tecnológicos do Rio Grande do Sul - Brasil : análise usando econometria espacial, 2013 - 2020 - Gasparote, Mauricio (2023)
This dissertation consists of an evaluation of the impacts of Science and Technology Parks (STPs) on the number of jobs in knowledge-intensive occupations in the locations that host these arrangements and, in their neighborhoods, comprising the municipalities of the state of Rio Grande do Sul (RS). The work used eight-year data, covering analyzes between the periods from 2013 to 2020, observing information on education (number of doctors, masters, specialists, graduates in higher education and technical courses), number of service companies, number of industries and appropriate income, considering spatial components. For this purpose, the methodology employed consisted of exploratory data analysis, spatial autocorrelation tests, construction of a spatial econometrics model, econometric tests, and analysis of the results. The results obtained by the econometric model show a positive contribution of STPs in the number of jobs in knowledge-intensive occupations in the municipalities that host them with spillover effects in the neighborhoods.